2021
DOI: 10.1091/mbc.e20-10-0625
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying cellular effects of human MEK1 mutations

Abstract: Terminal regions of Drosophila embryos are patterned by signaling through ERK, which is genetically deregulated in multiple human diseases. Quantitative studies of terminal patterning have been recently used to investigate gain-of-function variants of human MEK1, encoding the MEK kinase that directly activates ERK by dual phosphorylation. Unexpectedly, several mutations reduced ERK activation by extracellular signals, possibly through a negative feedback triggered by signal-independent activity of the mutant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…6B bottom, D-F). The same phenotype was previously reported for other gain-of function MEK1 mutants (60, 61). Notably, ∼60% of embryos expressing Q56P MEK1 failed to form any cuticle.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…6B bottom, D-F). The same phenotype was previously reported for other gain-of function MEK1 mutants (60, 61). Notably, ∼60% of embryos expressing Q56P MEK1 failed to form any cuticle.…”
Section: Resultssupporting
confidence: 86%
“…Previously, we found that mutations that cause lethality of Drosophila embryos belong to the gain-of-function type mutations (52). Gain-of-function mutations allow for signaling, even in the absence of upstream pathway activation, as well as a more rapid response to activation by RAF even in the absence of necessary adapter proteins (60-62). All three mutations significantly increased embryonic lethality (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MEK1 mutations, which are more frequent than those in MEK2, are also observed in many tumors such as melanoma, colorectal, lung, thyroid, and ovarian cancers 7 . These oncogenes ultimately hyperactivate ERK signaling and generate aberrant gene expression patterns that provoke cell overgrowth and/or a differentiation abnormality, thereby inducing cancer development and progression 8 , 9 . Targeting of these oncogenes for cancer therapy is therefore of particular interest, and their specific inhibitors (e.g., erlotinib, vemurafenib, and trametinib, inhibitors of EGFR, BRaf, and MEK, respectively) are currently in clinical use 10 .…”
Section: Introductionmentioning
confidence: 99%
“…These mutations were identified in treatment naïve tumors as well as in those resistant to MAPK targeted therapies 7,[9][10][11][12][13][14][15] . A number of MAP2K1 mutations have been demonstrated to be oncogenic via their ability to transform non-cancerous cells, or by increasing the phosphorylation of downstream ERK 10,11,13,[16][17][18][19][20][21][22][23][24][25][26][27][28] . In 2018, Gao et al proposed a classification system for MAP2K1 mutations 2,13 .…”
Section: Introductionmentioning
confidence: 99%